Culture-Based Education Innovation for Children's Character Building in the Context of Educational Tourism Destinations - Riyanto Riyanto; Hefry Johan Ferdhianzah; Hendrik Trilaksono (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to explore the innovation of culture-based education as an effort to build children's character in the context of educational tourism destinations. Against the background of the multi-dimensional crisis faced by the nation, learning of culture becomes very strategic to revive patriotism and maintain cultural diversity. This research method uses a descriptive qualitative approach. Data were collected through literature studies, Field observation of educational tourism destinations and how the interaction between learners and the environment takes place, and interview with policy makers and community leaders. The research findings highlighted the need for serious efforts in storing, preserving, and resurfacing scattered cultural data, especially related to oral traditions, manuscripts, customs, rites, traditional knowledge, traditional technology, arts, languages, folk games, and traditional sports. The results reflect the need to focus on strengthening governance related to local traditions, as well as efforts to empower communities through cultural tourism as a source of foreign exchange. In addition, the research highlighted the challenges of saving traditional technologies, local languages, traditional arts and folk games that are in danger of fading away. The research conclusion emphasizes the urgency of promoting culture, literature, and preserving historical traces as an integral part of children's character building efforts. Thus, understanding and love for cultural values can be passed on to the younger generation, strengthening awareness of national identity, and preventing the loss of traditional values amid globalization.